2015
DOI: 10.1038/ncomms9559
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study identifies multiple susceptibility loci for glioma

Abstract: Previous genome-wide association studies (GWASs) have shown that common genetic variation contributes to the heritable risk of glioma. To identify new glioma susceptibility loci, we conducted a meta-analysis of four GWAS (totalling 4,147 cases and 7,435 controls), with imputation using 1000 Genomes and UK10K Project data as reference. After genotyping an additional 1,490 cases and 1,723 controls we identify new risk loci for glioblastoma (GBM) at 12q23.33 (rs3851634, near POLR3B, P=3.02 × 10−9) and non-GBM at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
107
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(110 citation statements)
references
References 69 publications
(85 reference statements)
2
107
0
1
Order By: Relevance
“…This led to the identification of rs55705857 as being responsible for the 8q24.21 glioma association, with the SNP exhibiting a much larger effect size than the initial GWAS tagSNPs and being highly restricted to low-grade IDH-mutated glioma (28, 34). Following on from this, in 2015, a GWAS was carried out by Kinnersley and colleagues (25), making use of datasets from Sanson and colleagues (31) as well as an independent replication series, in total comprising 5,637 cases and 9,158 controls. This study identified five new glioma risk loci, one for GBM at 12q23.33 ( POLR3B ), and four for non-GBM gliomas at 10q25.2 ( VTI1A ), 11q23.2 ( ZBTB16 ), 12q21.2, and 15q24.2 ( ETFA ).…”
Section: Chronological History Of Glioma Risk Loci Discoverymentioning
confidence: 99%
“…This led to the identification of rs55705857 as being responsible for the 8q24.21 glioma association, with the SNP exhibiting a much larger effect size than the initial GWAS tagSNPs and being highly restricted to low-grade IDH-mutated glioma (28, 34). Following on from this, in 2015, a GWAS was carried out by Kinnersley and colleagues (25), making use of datasets from Sanson and colleagues (31) as well as an independent replication series, in total comprising 5,637 cases and 9,158 controls. This study identified five new glioma risk loci, one for GBM at 12q23.33 ( POLR3B ), and four for non-GBM gliomas at 10q25.2 ( VTI1A ), 11q23.2 ( ZBTB16 ), 12q21.2, and 15q24.2 ( ETFA ).…”
Section: Chronological History Of Glioma Risk Loci Discoverymentioning
confidence: 99%
“…Sickle Hb molecules are known to undergo repeated polymerization/depolymerization with formation of greater amounts of reactive oxygen species (O 2 -), which do lead to a reaction cascade such as blood cell adhesion, vaso-occlusion, ischemia reperfusion injury and hemolysis [74]. Oxidative stress challenges often arise from sources such as radiation, metabolism of xenobiotic, and challenges to the immune system due to abnormal functions [56,75].…”
Section: Oxidative Stress In Scd Patho-biologymentioning
confidence: 99%
“…Eugenol, capsaicin, and piperine that have many characteristics attributes (Table 4), may further help in SCD management. Similarly, KLF1 (an erythroid specific transcription factor) associated with globin expression and erythropoiesis with influence in the switching of HbF to HbA [74,78,79] can be targeted in a holistic manner, encompassing medicinal plants that could be useful in the delay switching process. We think this is an important concept, considering the fact that reduced expression of KLF1 in human erythroblast cell line is linked to viability and differentiation [30], which ameliorates -thalassemia and SCD phenotypic complications [45].…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%
“…Gliomas were composes of several subtypes, mainly including Glioblastomas, which account for approximately 60 to 70%, anaplastic astrocytomas, which account for 10 to 15%, and anaplastic oligodendrogliomas and anaplastic oligoastrocytomas, which account for 10% [3,[8][9][10][11]. To present, only a small proportion of the genetic factors for gliomas has been yet established, including results of familial studies, candidate gene studies, and genomewide association studies (GWASs) [12][13][14][15][16]. Understanding of the genetic basis is a key component of preventive oncology.…”
Section: Introductionmentioning
confidence: 99%